Asymmetric mean reversion in low liquid markets: Evidence from BRVM - Nathaniel Gbenro; Richard Kouamé Moussa (Journal of Risk and Financial Management, 2019)
This paper analyzes the mean reversion property on the west African stock market (in French, Bourse Régionale des Valeurs Mobilières BRVM). For this purpose, we use two daily indices: (i) the composite index (BRVMC) and (ii) the index of the 10 most liquid assets (BRVM10) collected from 3 January 2005 to 29 June 2018. We estimate an asymmetric nonlinear autoregressive model with an EGARCH innovation to account for heteroskedasticity. The results suggest the existence of a mean reversion property for both indices. The half-life time is 7 days for the composite index and 2 days for the BRVM 10 index. Furthermore, using a rolling regression technique, we show that the estimated half-life time declines slightly for the composite index.
Keywords: C58; G14; G15; 330; stock market efficiency; mean reversion; half-life; asymmetry; rolling regression